(untitled) (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract: The research focused on explaining the role of the United States of America in confronting extremism, especially its role in confronting ISIS the ISIS front as a model for this confrontation, and statement of strategies that the United States follows in this confrontation. Within its structure, the research includes terms related to the topic in full as well as, explaining the emergence of ISIS in the major areas in Iraq, especially this organization whose activity may be very clear in Iraq, as it controls several Iraqi cities and provinces, causing destruction and devastation, spreading panic, and finally, explaining the role of the United States in confronting this .in general . Among the most important findings of the research are: The most prominent strategies of spending terror controlling were through containment and rebellion. The organization used violence for the purpose of intelligence in society, especially through social media. On the other side ,there was limited in the collective groups to confront extremism in Iraq and the official rule, which is linked to the military and security establishment, especially with noticeable weakness among civil institutions (in terms of civil society) and governmental institutions. The jihadist group had a clear prominent effectiveness in eliminating ISIS liberating Iraqi cities and provinces controlled by the organization. Keywords: international actors, extremism, the United States of America, ISIS.